The following linear equation

$$-x \frac{a}{b^2} + c \frac{1}{b^2} = 0 \tag{1}\label{eq1}$$

is such that $a, b, c \in \mathbb{R}$. It must be evaluated for $b \to 0$.

  1. It can be solved immediately by multiplying both sides by $b^2$:

$$-xa + c = 0$$ $$x = \frac{c}{a} \tag{2}\label{eq2}$$

  1. Otherwise,

$$x \frac{a}{b^2} = c \frac{1}{b^2}$$ $$x = \frac{b^2}{b^2} \frac{c}{a} = \frac{c}{a} \tag{3}\label{eq3}$$

If both sides of an equation are multiplied by a non-zero quantity, the new equation is equivalent to the original one, as stated in a well-known property. But is this property is still valid if the quantity is infinitesimal, as here? Why?

My attempt:

In the procedure 2, leading to $\eqref{eq3}$, the fraction $b^2 / b^2$ is unitary: it's easier to accept that it's correct, regardless of the value of $b^2$.

However, with equations like $\eqref{eq1}$ (and more complex cases), it's a common practice to immediately follow the procedure 1. I wonder if it's still correct and why.


1 Answer 1


Yes, this is valid.

One way of looking at this is to consider $b = \frac 1t, t \to \infty$. The equation then resolves to $$t^2(-xa+c) = 0$$ Since $t^2$ tends to infinity and the RHS is zero, we must have $-xa + c = 0 \implies x = \frac ca$.

Another way of looking at it would be that an infinitesimal is a finite number $\epsilon$ such that $\epsilon > 0$ and $\epsilon \to 0$. Thus, the infinitesimal is not exactly zero, but is very, very close to zero and hence multiplying both sides by said infinitesimal does not change the equation.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.